Hearing impairment locus heterogeneity and identification of PLS1 as a new autosomal dominant gene in Hungarian Roma - Schrauwen, Isabelle; Melegh, Béla I; Chakchouk, Imen; Acharya, Anushree; Nasir, Abdul; Poston, Alexis; Cornejo-Sanchez, Diana M; Szabo, Zsolt; Karosi, Tamás; Bene, Judit; Melegh, Béla; Leal, Suzanne M (European journal of human genetics : EJHG, 2019)
Roma are a socially and culturally distinct isolated population with genetically divergent subisolates, residing mainly across Central, Southern, and Eastern Europe. We evaluated the genetic etiology of hearing impairment (HI) in 15 Hungarian Roma families through exome sequencing. A family with autosomal dominant non-syndromic HI segregating a rare variant in the Calponin-homology 2 domain of PLS1, or Plastin 1 [p.(Leu363Phe)] was identified. Young adult Pls1 knockout mice have progressive HI and show morphological defects to their inner hair cells. There is evidence that PLS1 is important in the preservation of adult stereocilia and normal hearing. Four families segregated the European ancestral variant c.35delG [p.(Gly12fs)] in GJB2, and one family was homozygous for p.(Trp24*), an Indian subcontinent ancestral variant which is common amongst Roma from Slovakia, Czech Republic, and Spain. We also observed variants in known HI genes USH1G, USH2A, MYH9, MYO7A, and a splice site variant in MANBA (c.2158-2A>G) in a family with HI, intellectual disability, behavioral problems, and respiratory inflammation, which was previously reported in a Czech Roma family with similar features. Lastly, using multidimensional scaling and ADMIXTURE analyses, we delineate the degree of Asian/European admixture in the HI families understudy, and show that Roma individuals carrying the GJB2 p.(Trp24*) and MANBA c.2158-2A>G variants have a more pronounced South Asian background, whereas the other hearing-impaired Roma display an ancestral background similar to Europeans. We demonstrate a diverse genetic HI etiology in the Hungarian Roma and identify a new gene PLS1, for autosomal dominant human non-syndromic HI.